Perjanjian Koeksistensi Merek dan Letter of Consent terhadap Merek yang Memiliki Unsur Persamaan pada Pokoknya - Yelma Nomida Alvisalia (Syntax Corporation Indonesia, 2024)
A trademark serves as the identity of a product and/or service, representing the quality and reputation associated with it. In the process of trademark registration, it is inevitable that several trademarks may bear similarities and are at risk of rejection by the Directorate General of Intellectual Property (DGIP). To address this issue, some strategies include the establishment of Trademark Coexistence Agreements or Letters of Consent (LOC). This research aims to explore the roles of Trademark Coexistence Agreements and LOCs in overcoming the challenges of registering trademarks that share similarities. The methodology employed is normative legal research, involving analysis of relevant legislation and secondary data from related literature. The findings indicate that both Trademark Coexistence Agreements and LOCs can assist trademark owners in reaching agreements regarding the use of similar trademarks. However, the application of these instruments in Indonesia has not been explicitly regulated. The conclusion of this study underscores the necessity for clearer legislative policies and support for the practice of utilizing Trademark Coexistence Agreements and LOCs to streamline the trademark registration process and promote innovation in the market.